2011
DOI: 10.1299/jmmp.5.251
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Short Coir Fibre Reinforced Poly(Butylene Succinate) Biodegradable Composites

Abstract: The poly(butylene succinate) (PBS) biodegradable composites reinforced with short coir fibres were fabricated by compression molding method. Effect of different fibre contents varying from 10 to 50 wt% on the mechanical and thermal properties of coir/PBS composites have been studied in terms of tensile and flexural properties, thermal stability, thermal expansion, dynamic mechanical properties, and microscopic observations. Tensile and flexural moduli of the composites were improved with the increase of fibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Below about 400°C, the thermal degradation of the composites increases with increasing the fiber content, but it decreases above 400°C. As a result, at low temperature region the thermal stability of the composites decreases with increasing the jute fiber content similar to the results reported in [30] for coir/PBS biodegradable composites. The percentage weight loss of jute/ PBS composites decreases with increasing the fiber content at 500°C ( Table 3).…”
Section: Tga Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Below about 400°C, the thermal degradation of the composites increases with increasing the fiber content, but it decreases above 400°C. As a result, at low temperature region the thermal stability of the composites decreases with increasing the jute fiber content similar to the results reported in [30] for coir/PBS biodegradable composites. The percentage weight loss of jute/ PBS composites decreases with increasing the fiber content at 500°C ( Table 3).…”
Section: Tga Analysissupporting
confidence: 86%
“…About 5% weight loss of UT jute was observed in first stage because of absorbed moisture. The initial weight loss around 60°C can be due to the evaporation of water in the jute fiber; therefore, it is not significant weight loss in the range of 100-250°C approximately Advanced Composite Materials 253 similar with the decomposition behavior of other natural fibers, such as kenaf [29], coir [30], silk [31], and wood [32]. The second transition occurs from 250 to 370°C, jute fiber undergoes thermal degradation of cellulose and hemicellulose substances.…”
Section: Tga Analysismentioning
confidence: 99%
“…Utilization of natural fibers in composite preparation offer several advantages compared to those of synthetic fibers which include low density, low cost, renewability, and biodegradability [4,5]. Natural fibers like kenaf [3,6], jute [2,5], coir [7], silk [8], bamboo [9], sisal [10], and oil palm empty fruit bunch [11][12][13] have been extensively studied for fabrication of polymer/fiber composites. Rozman et al [11] reported that incorporation of the OPEFBF into polypropylene matrix resulted in an improved tensile modulus but reduced in tensile strength, elongation at break, and impact strength with increasing fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, polybutylene succinate (PBS) is a new, green, and eco-friendly material that has good mechanical properties, good heat and chemical resistance, and complete biodegradability. PBS can also be completely burned without producing any toxic gas [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it improves the performance of biodegradable composites, aids in their development, and helps lower the costs of the composites, considering that 1 t of cassava residue costs 900 yuan (approximately $ 129.71). The composite materials could be applied in packaging, construction (for example, wood flooring) and other fields [11], thus offering broad and significant application prospects. Meanwhile, polybutylene succinate (PBS) is a new, green, and eco-friendly material that has good mechanical properties, good heat and chemical resistance, and complete biodegradability.…”
Section: Introductionmentioning
confidence: 99%